HEALTH-RELATED QUALITY OF LIFE (HRQOL) IN TYPE 2 DIABETES PATIENTS WITH PAINFUL NEUROPATHY BEFORE AND AFTER 6 WEEKS PREGABALIN THERAPY.: Pharmaceutical Science-Medicine - SULTAN, INTESSAR; ABOZED, OLFAT; ALKHOULY, NASHWA; EMAN NAGUIB OSMAN; ALDUHAILIB, HASSAN; ALOTAIBI, MEES (International Journal of Life Science and Pharma Research, 2019)
Painful Diabetic Neuropathy (PDN) is associated with a significant reduction in health-related quality of life (HRQOL). Glycemic control and improving HRQoL are now recognized as the main goals of patientcentered diabetes care. This pre-post quasi study aimed to assess HRQoL in type 2 diabetic patients with PDN before and after pregabalin therapy from October 2017 to April 2018. Adult Saudis outpatients (N=103) with PDN, under no specific therapy, were selected from three private hospitals in Jeddah, Saudi Arabia. Neuropathy Symptom Score, Numeric Rating Scale (NRS-11), neurological examination, 10 gm monofilament, and Ewing’s reflex tests were used for assessment. All enrolled patients received pregabalin 75 mg once for 1 week followed by twice daily; then higher doses were used based on response (median dose 150 mg for 6 weeks). Weekly follow up was performed for patient’s severity using NRS-11 and for drug side effects. HRQOL was assessed before and 6 weeks after pregabalin therapy using the Arabic version of The RAND 36-item Health Survey. Patients had severe PDN (median of 7), poor metabolic control (median A1C of 9.1) and disabling both mental (36.71) and physical summary scores (32.50) of HRQoL (both below 50). Higher baseline A1C was significantly associated with higher pain severity (r=0.467, p=0.000) and lower pain score-QoL (r=-0.267, p=0.006). After 6 weeks of therapy, significant improvements were detected in pain severity, metabolic control and all subparameters of HRQoL (p=0.000 for all). The major side effect was dose-dependent somnolence (18%). Uncontrolled type 2 adult Saudi patients with severe PDN have disabling HRQoL. Six weeks of pregabalin therapy was safe and effective and was associated with the improvement of physical and mental parameters of HRQoL. Given its recent restrictions in Saudi Arabia, risk of misuse and dependency, other therapeutic modalities for these patients should be similarly investigated.